2017
DOI: 10.1086/689289
|View full text |Cite
|
Sign up to set email alerts
|

Combined oral administration of L‐arginine and tetrahydrobiopterin in a rat model of pulmonary arterial hypertension

Abstract: Alterations in the nitric oxide (NO) pathway play a major role in pulmonary arterial hypertension (PAH). L-arginine (LA) and tetrahydrobiopterin (BH4) are main substrates in the production of NO, which mediates pulmonary vasodilation. Administration of either LA or BH4 decrease pulmonary artery pressure (PAP). A combined administration of both may have synergistic effects in the therapy of PAH. In a telemetrically monitored model of unilateral pneumonectomy and monocrotaline-induced PAH, male Sprague-Dawley ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…BH 4 levels are decreased in many models of cardiovascular disease [ 30 ] including hypertension [ 31 ]. A role for BH 4 in BP control is further supported by the finding that BH 4 supplementation lowers BP in a male rat model of pulmonary arterial hypertension [ 32 ] and male mice with disrupted BH 4 synthesis are hypertensive [ 33 ]. Despite growing interest and evidence for the role of BH 4 in the pathogenesis of hypertension, there is a scarcity of data in the literature examining the impact of sex on the BH 4 system.…”
Section: Discussionmentioning
confidence: 99%
“…BH 4 levels are decreased in many models of cardiovascular disease [ 30 ] including hypertension [ 31 ]. A role for BH 4 in BP control is further supported by the finding that BH 4 supplementation lowers BP in a male rat model of pulmonary arterial hypertension [ 32 ] and male mice with disrupted BH 4 synthesis are hypertensive [ 33 ]. Despite growing interest and evidence for the role of BH 4 in the pathogenesis of hypertension, there is a scarcity of data in the literature examining the impact of sex on the BH 4 system.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with evidence that supplementation of BH4 [ 116 , 123 , 124 , 125 , 126 ] and an increased BH4/oxidized BH4 ratio [ 31 , 121 , 123 ] enhance eNOS activity, oral BH4 administration promotes eNOS activity, lowers lung O 2 .− levels, and reverses established CH-induced PH [ 34 ]. Additionally, BH4 is shown to be beneficial in the treatment of a rat PAH model [ 127 ].…”
Section: Ros In the Pathogenesis Of Phmentioning
confidence: 99%
“…The present investigation showed that pre-incubation of rat aortic rings with LA and BH 4 in combination caused the marked increase in BQ-123 efficacy and potency. Schreiber et al (2017) recorded that LA is the main substrate in the production of NO. Binding BH 4 exert allosteric action to stabilize the active dimeric form of eNOS (Shinozaki et al, 2000) and increases the enzymatic turnover of LA.…”
Section: Discussionmentioning
confidence: 99%